Determination of Arctiin in Fengre Ganmao Granules by Capillary Electrophoresis. Issue 2 (February 2020) - Zhao, Meili; Liu, Haixing; Zhang, Zongbao; Wang, Lintong
Abstract: This paper investigated the determination of arctiin content in Fengre Ganmao granules by high performance capillary electrophoresis (HPCE) method. The borax solution of 37.5 mmol concentration containing 12.5% methanol was chosen as buffer solution. The experiment was performed at a constant voltage of 16 kV and UV detection wavelength of 277 nm. The content of arctiin in Fengre Ganmao granules was 10.307mg/g (RSD=5.8%) (n=6). The recovery was in the range of 90.5%-115.1% (n=5). This method is suitable for the detection of the content of arctiin in Fengre Ganmao granules.